Role of haemorheological factors in patients with retinal vein occlusion - Sofi, Francesco; Mannini, Lucia; Marcucci, Rossella; Bolli, Paola; Sodi, Andrea; Giambene, Barbara; Menchini, Ugo; Gensini, Gian Franco; Abbate, Rosanna; Prisco, Domenico (Thrombosis and Haemostasis, 2007)
Retinal vein occlusion (RVO) is an important cause of permanent visual loss. Hyperviscosity, due to alterations of blood cells and plasma components, may play a role in the pathogenesis of RVO. Aim of this case-control study was to evaluate the possible association between haemorheology and RVO. In 180 RVO patients and in 180 healthy subjects comparable for age and gender we analysed the whole haemorheological profile: [whole blood viscosity (WBV), erythrocyte deformability index (DI), plasma viscosity (PLV), and fibrinogen]. WBV and PLV were measured using a rotational viscosimeter, whereas DI was measured by a microcomputer-assisted filtrometer. WBV at 0.512 sec-1 and 94.5 sec-1 shear rates as well as DI, but not PLV, were found to be significantly different in patients as compared to healthy subjects. At the logistic univariate analysis,a significant association between the highest tertiles of WBV at 94.5 sec-1 shear rate (OR:4.91,95%CI 2.95–8.17;p<0.0001),WBV at 0.512 sec-1 shear rate (OR: 2.31, 95%CI 1.42–3.77; p<0.0001), and the lowest tertile of DI (OR: 0.18, 95%CI 0.10–0.32; p<0.0001) and RVO was found. After adjustment for potential confounders,the highest tertiles of WBV at 0.512 sec-1 shear rate (OR: 3.23, 95%CI 1.39–7.48; p=0.006),WBV at 94.5 sec-1 shear rate (OR: 6.74, 95%CI 3.06–14.86; p<0.0001) and the lowest tertile of DI (OR:0.20,95%CI 0.09–0.44,p<0.0001) remained significantly associated with the disease. In conclusion,our data indicate that an alteration of haemorheological parameters may modulate the susceptibility to the RVO, by possibly helping to identify patients who may benefit from haemodilution.
Keywords: Blood viscosity; haemodilution; haemorheology; retinal vein occlusion